Remotely sensed C3 and C4 grass species aboveground biomass variability in response to seasonal climate and topography. (29th April 2019) - Shoko, Cletah; Mutanga, Onisimo; Dube, Timothy
Abstract: Seasonal climate and topography influence C3 and C4 grass species aboveground biomass (AGB). Climate change further threatens these grasses AGB, thereby compromising their ability to provide ecosystem goods and services. This emphasises the need to monitor their AGB for well‐informed management. New‐generation sensors, with improved resolution capabilities present an opportunity to explore C3 and C4 AGB. This study therefore investigated the response of remotely sensed C3 and C4 grasses AGB to seasonal climate and topography. Overall, the spatial and temporal responses of AGB due to seasonal climate and topography were observed across the study area. For example, in March, a marked increase in C4 AGB was associated with an increase in rainfall, with the highest significant positive relationship ( R 2 = 0.82, p < 0.005). Elevation had very significant positive relationship ( R 2 = 0.84; p < 0.005) with C3 and highest negative ( R 2 = −0.77; p < 0.005) with C4 AGB. During the winter fall, AGB significantly decreased from averages of 2.592 and 1.101 kg/m 2 in winter (May), to 0.718 and 0.469 kg/m 2 in August, for C3 and C4 grasses, respectively. These findings provide a key step in monitoring rangelands and assessing management practices to boost productivity. Résumé: Le climat saisonnier et la topographie influencent des espèces de graminées C3 et C4 sur la biomasse aérienne (AGB). Le changement climatique menace davantage ces graminées AGB, compromettant ainsi leur capacité à fournir des biens et services liés à l'écosystème. Cela souligne la nécessité de surveiller leur AGB pour une gestion bien informée. Les capteurs de nouvelle génération, dotés de capacités de résolution améliorées, offrent l'occasion d'explorer les C3 et C4 AGB. Cette étude a donc examiné le résultat des graminées AGB C3 et C4 à télédétection au climat saisonnier et à la topographie. Dans l'ensemble, les résultats spatiaux et temporels de l'AGB en raison du climat saisonnier et de la topographie ont été observés dans la zone d'étude. Par exemple, en mars, une augmentation marquée de l'AGB C4 a été associée à une augmentation des précipitations, avec la relation positive significative la plus élevée (R2 = 0, 82, P <0, 005). L'élévation a eu une relation positive très significative (R2 = 0, 84; P <0, 005) avec C3 et la plus négative (R2 = ‐0, 77; P <0, 005) avec C4 AGB. Au cours de l'automne, l'ABG a considérablement diminué, passant de 2, 592 kg / m2 et 1, 101 kg / m2 en hiver (mai) à 0, 718 kg / m2 et 0, 469 kg / m2 en août, respectivement pour les graminées C3 et C4. Ces résultats constituent une étape clé dans la surveillance des pâturages et l'évaluation des pratiques de gestion pour à accroître la productivité.